Technologies for women - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
The Institute for Agricultural Research of Ahmadu Bello University, Nigeria undertook a two-year study aimed at developing and testing appropriate technology for rural women in Nigeria. Supported by a grant from the Ford Foundation Project, the...